THE EFFECT OF DIE/PUNCH RADIUS AND DRAWING RATIO ON THE WALL THICKNESS IN DEEP DRAWING DIES - Ozek, Cebeli; Bal, Muhammet (Gazi Univ, Fac Engineering Architecture, 2009)
Deep drawing is one of the most important methods used to form sheet materials. The production of optimal products in this process is dependent on the process variables such as blank shapes, profile radius of punch and die, and formability of materials. A specially, the blank shape is very important since it controls the formability directly. This study presents an attempt to determine the effect of various radiuses of die and punch, limit drawing ratio and die/blank holder angles on the wall thickness using DIN EN10130-91 sheet material. The die/blank holder profile with angles of alpha=2.5 degrees, alpha=7.5 degrees, alpha=12.5 degrees, alpha=15 degrees and die/punch profile with radiuses for R=10, R=8, R=6, R=4 mm. The punch have diameter of 30 mm and the die have a diameter of 32.3 mm, which gives 1.15 mm of clearance. Shell Tellus 68 oil was used between the die and the blank to reduce frictional resistance. The wall thickness was measured on six different zones of the cup. The experiments show that the wall thickness decreased with increasing limit drawing ratio (beta), die/blank holder angles (alpha) and die-punch radius (R).
Keywords: Deep drawing; limit drawing ratio; blank holder force; wall thickness